foF2 long-term trends at the southern crest of the equatorial anomaly - Elias, Ana Georgina (2006)
Long-term trends in the electron density of the ionosphere for the period 1957-1986 is studied using foF2 monthly median hourly data measured at Tucuman (26.9S, 65.4W), a station located at the southern crest of the equatorial anomaly. The linear trend for each hour and each month is estimated after filtering out the effects of solar activity. For the intervals 0-2 LT and 9-23 LT, during equinoxes and summer solstice, the trend is negative. Statistically null or slightly positive trends are observed for the interval 3-8 LT for every season, and for every hour of winter months. The daily amplitude of foF2 decreases since 1957 due to the decreasing trend in the maximum daily values and almost null-trended minimum daily values. A rough estimate, based on the dip angle trend (which in Tucuman has increased during the 30-year interval at a rate of 0.35%/year), indicates that negative foF2 trends should be expected during daytime hours, and positive trends during night-time hours, behaviour observed in the foF2 data here analyzed.